2017
DOI: 10.5937/tehnika1703403k
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of European railway companies efficiency: Application of a two-stage analysis

Abstract: The aim of this paper is efficiency assessment of railway companies from larger Europe during the most recent time period, taking into account different input-output configurations. For this aim, two-stage analysis is employed, where efficiency scores are obtained by DEA in the first stage, while in the second stage different statistical tests are conducted and Tobit analysis is used in order to evaluate influence of different environmental factors. It has been found that railways were oriented either on passe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…For research on the influencing factors of transport efficiency, the methods usually include qualitative analysis, Tobit method, multiple regression method, Stochastic Frontier Analysis (SFA) and panel regression, etc. Kapetanovic et al [6] used the Tobit regression method and concluded that per capita GDP, population density, the existence of double/multi-track lines, and the percentage of electrified lines have significant positive effects on passenger transport efficiency. Catalano et al [7] provides information about the frequency of occurrence of different input measures in efficiency studies for railways.…”
Section: Literature Review and Innovation Of This Papermentioning
confidence: 99%
See 1 more Smart Citation
“…For research on the influencing factors of transport efficiency, the methods usually include qualitative analysis, Tobit method, multiple regression method, Stochastic Frontier Analysis (SFA) and panel regression, etc. Kapetanovic et al [6] used the Tobit regression method and concluded that per capita GDP, population density, the existence of double/multi-track lines, and the percentage of electrified lines have significant positive effects on passenger transport efficiency. Catalano et al [7] provides information about the frequency of occurrence of different input measures in efficiency studies for railways.…”
Section: Literature Review and Innovation Of This Papermentioning
confidence: 99%
“…(5) The newly built Line 6 can improve the scale efficiency of the system. (6) The newly built Changping Line cannot improve the scale efficiency of the system. (7) In combination optimization, under the conditions of original passenger flow and original departure interval, the shadow efficiency of the two schemes of removing the Changping Line and Line 6 is inconsistent with that of the single factor simulation experiment, and the relationship between shadow efficiencies also changes, which proves that the shadow efficiency is marginal efficiency, which is related to the starting point of the original scheme.…”
Section: Analysis Conclusionmentioning
confidence: 99%
“…Currently, many research in the field of transport use various methods and approaches to analyze the competitive environment and identify measures to strengthen the position in the market [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. For example, in [1] the authors use a stylized simulation model to study how open access competition affects tariffs, demand, supply, consumer surplus, and operator profits compared to a profit-maximizing monopoly and a situation where welfare.…”
Section: Introductionmentioning
confidence: 99%